GLP‑1 RECEPTOR AGONISTS IN THE MANAGEMENT OF OBESE WOMEN WITH POLYCYSTIC OVARY SYNDROME: EFFECTS ON BODY WEIGHT, METABOLIC PROFILE, AND REPRODUCTIVE FUNCTION – A LITERATURE REVIEW - Mularczyk, Patrycja; Polek, Nina; Sikorska, Małgorzata; Łysoniewski, Wojciech; Marcysiak, Artur; Mruzek, Tomasz; Kiełbasiewicz, Magdalena; Zawadzka, Karolina (International Journal of Innovative Technologies in Social Science, 2026)
Objective: This dissertation synthesizes contemporary evidence on glucagon-like peptide-1 (GLP-1) receptor agonists in women with polycystic ovary syndrome (PCOS) and obesity, with emphasis on body weight, metabolic parameters, and reproductive outcomes.Methods: A narrative–systematic review (2012–2025) included randomized clinical trials, meta-analyses, and systematic and narrative reviews from PubMed, Embase, the Cochrane Library, Web of Science, and other databases. Studies of liraglutide, semaglutide, exenatide, and dulaglutide, as monotherapy or combined with metformin in women with PCOS, were analyzed with respect to anthropometric, metabolic, hormonal, and reproductive endpoints.Results: GLP-1 receptor agonists generally achieved greater reductions in body weight, BMI, and waist circumference than lifestyle modification or metformin alone, alongside improvements in insulin sensitivity, glycaemic control, and selected lipid measures. Decreases in androgen levels, attenuation of clinical hyperandrogenism, and improved menstrual regularity, ovulation rates, and pregnancy rates were reported, particularly in obese, markedly insulin-resistant women. Adverse events were mainly transient gastrointestinal symptoms.Conclusions: GLP-1 receptor agonists appear to be a promising adjunct to standard treatment of obese women with PCOS, enabling more effective weight loss, metabolic improvement, and potentially better cardiovascular prognosis, together with enhanced ovulatory and pregnancy outcomes. Nevertheless, the short duration of most studies, absence of safety data in pregnancy, and the requirement for contraception and wash out before conception highlight the need for long-term randomized trials evaluating efficacy, safety, and hard reproductive and cardiovascular endpoints.